The QC Problem Solving Approach: Solving Workplace Problems the Japanese Way - Hosotani, Katsuya (Madras: Productivity Press (India) Pvt Ltd, 2005)
The three main features of the Japanese QC problem-solving approach are:1. It adopts a particular way of looking at things that leads naturally to the solution of problems.2. It uses a tried-and-tested problem-solving procedure that follows a set pattern.3. It employs scientific methods to unravel complex problems. Thanks to powerful features like these, the QC problem-solving approach has achieved superlative results in every area of Total Quality Management. Drawing on real-life examples, this book clearly explains the QC problem-solving approach, how to promote problem-solving, and how to use QC tools. It is essential reading for all work-place leaders-from shop-floor supervisors and QC circle personnel to line managers and staff.
The Importance of Problem Solving -- What is the QC Problem-Solving Approach -- The QC Viewpoint-Vital for QC-Type Problem Solving -- The QC Seven-Step Formula-Solving Problems the QC Way -- The QC Tools -- Some Examples of the QC Problem-Solving Approach
Includes index
Keywords: Statistics; Quality Control -- Workplace Problems -- Japan